PROGRAMMING ANALYSIS FOR THE AIRSIDE FACILITY DEVELOPMENT OF KERTAJATI INTERNATIONAL AIRPORT BY USING SIMULATION APPROACH - Andiani, Mirza
Before Kertajati Airport started to operate, the inbound and outbound flights of the Province of West Java were served by Husein Sastranegara Airport, which currently belongs to the Indonesian Air Force with a capacity of 4.3 million passengers per year. Along with the role of the Province of West Java who has three National Activity Centers (PKN) and three Provincial National Activity Centers, a new airport establishment is needed to furtherly serve the Province of West Java’s demand, especially for the international flight routes. Since 2018, Kertajati Airport has been operating with the target of 1.7 million passengers in 2019. However, the number of passengers served by Kertajati Airport in 2019 only reached up to 460 thousands of passengers. With such consideration along with the mandate from the Minister of Transportation in appointing Kertajati Airport as the Hajj and Umrah Airport in West Java, it is necessary to redesign the development stages for Kertajati Airport by using a simulation approach. The design of the development stages of Kertajati Airport was carried out based on the increasing demand of the passenger movement and the role of Kertajati Airport as Hajj and Umrah Airport in West Java. According to the development analysis based on the demand of the passenger movements and cost estimation, the design for the geometric development of Kertajati Airport is as follows: Runway 1 length extension to 3,500 meters (2023), additional parallel taxiway for runway 1 (2033), and additional runway 2 along with a single parallel taxiway configuration (2038). In addition, based on the results of the overlay thickness design and the evaluation of the pavement overlay design results, the required overlay is a Hot-Mixed Asphalt (HMA) material with a thickness of 50.8 mm for every 5 years. Moreover, there will also be the development of aircraft parking stand for each year of the development according to the increasing number of passengers. Based on the evaluation of the availability of Kertajati Airport’s accessibility which was carried out in 14 districts/cities in the Province of West Java (both before and before the Cisumdawu Toll started operating), there were 11 districts/cities that had better accessibility to Kertajati Airport in comparation to Soekarno-Hatta Airport. In addition, the capacity of the Cisumdawu toll road (464,600 passengers/day) is still able to offer passenger deals at Kertajati Airport in 2038 (110.030 passengers/day).